Spiritual Perspectives and Well-Being among Stroke Patients in Rehabilitation Centres of Four Tertiary Care Hospitals of Pakistan: Wellbeing of Stroke Patients in Rehabilitation Centres - Suliman, Muhammad; Sohail, Muhammad; Yaseen, Muhammad; Sultan, Amir; ., Adnan; G. Reed, Pamela (THE THERAPIST (Journal of Therapies & Rehabilitation Sciences), 2022)
Spiritual wellness acknowledges our search for deeper meaning in life. Spirituality can make it easier to cope with the physical and cognitive consequences of a stroke, as well as with any other illness. Objective: To identify spiritual well-being and perspective of stroke patients and its association. Methods: A total of 420 stroke patients with Epi info sample size calculator were selected from the rehabilitation centres of the tertiary care hospitals of Peshawar, Abbottabad and Swat. Responses recorded through demographic section as well as reliable and validated Likert type quantitative tools in an analytical cross-sectional study. Results: Of the 420 participants, 164 (39%) were female. The Spiritual Index of Well-being Scale (SIWB) had a mean score of 40.83 out of a possible 60 and the Spiritual Perspective Scale (SPS) had a mean score of 49.06 out of a possible 60. Spiritual perspectives and well-being were reported to be statistically significant (p < 0.05) with each other and with several of the demographic indices on ANOVA and post hoc tests (Games-Howell). The Pearson association between spiritual perspectives and wellbeing (r) was likewise shown to be positively highly statistically significant (r = 0.530, p < 0.000). Conclusions: The findings of the research complement and justify Reed's theory's theoretical assertions. Spiritual Perspectives and practises serve as a buffer and contribute to the growth of Spiritual Well-being. The inclusion of spiritual health as a component of holistic health during medical interventions has implications.